No Joke : Making Jewish Humor - Wisse, Ruth R. (Book collections on Project MUSE., 2013)
Humor is the most celebrated of all Jewish responses to modernity. In this book, Ruth Wisse evokes and applauds the genius of spontaneous Jewish joking--as well as the brilliance of comic masterworks by writers like Heinrich Heine, Sholem Aleichem, Isaac Babel, S.Y. Agnon, Isaac Bashevis Singer, and Philip Roth. At the same time, Wisse draws attention to the precarious conditions that call Jewish humor into being--and the price it may exact from its practitioners and audience. Wisse broadly traces modern Jewish humor around the world, teasing out its implications as she explores memorable and telling examples from German, Yiddish, English, Russian, and Hebrew.